Effects of Protein Restriction and Succedent Realimentation on Jejunal Function and Bacterial Composition of Different Colonic Niches in Weaned Piglets - Wang, Jue; Zhu, Yizhi; Tian, Shiyi; Shi, Qing; Yang, Huairong; Wang, Jing; Zhu, Weiyun (Frontiers in Veterinary Science, 2022)
Recent studies proved that protein succedent realimentation could rescue the loss of growth performance of weaning piglets caused by a prior protein restriction. However, how the protein restriction and succedent realimentation influenced the jejunal function and bacterial composition of different colonic niches microbiota in weaning piglets needs a further investigation. After protein succedent realimentation, we found that the treatment group (TRE) piglets had a higher IGF-1 content and IGF-1R gene expression level in jejunal mucosa than the control group (CON) piglets . The ZO-1 gene expression level was up-regulated in TRE piglets jejunal mucosa during protein restriction and succedent realimentation, while the jejunal permeability of TRE piglets was only decreased after protein succedent realimentation. In addition, we found that protein restriction and succedent realimentation increased the gene expression of Pept-1 and the fecal apparent digestibility of crude protein in TRE piglets, but decreased the fecal nitrogen content. After 16S rRNA MiSeq sequencing of bacteria in different colonic niches (mucosa and digesta), TRE piglets had a higher relative abundance of beneficial bacteria and a lower relative abundance of potential pathogens than CON piglets in different colonic niches after protein restriction and succedent realimentation. Our data showed that protein restriction and succedent realimentation decreased the concentrations of branch chain fatty acids (BCFAs) and ammonia-N in TRE piglets colon. In addition, protein succedent realimentation increased the concentration of total short chain fatty acids (SCFAs) in TRE piglets colon. All these findings demonstrated that the strategy of protein restriction and succedent realimentation is an effective way to improve intestinal health of weaning piglets, and provides new insights into the nutrition management of piglets during the weaning period.